Implementasi Pretreatment Ekstraksi Lipid untuk Produksi Biodiesel Nannochloropsis sp. yang Dikultivasi dalam Media Limbah Budidaya Vaname - Rusydi, Rachmawati; Alfaini, Momika; Ayuzar, Eva; Hartami, Prama; Salamah, Salamah; Muliani, Muliani; Khalil, Munawwar; Febri, Suri Purnama (Jurnal Ilmiah Samudra Akuatika, 2024)
Nannochloropsis sp. is the green colored microalgae with its round shape of cell. This microalgae has lipids of 28,7% by dry weight, especially unsaturated fatty acids which can be transesterified to produce methyl ester and be a potential as biodiesel feedstock. The content of biodiesel Nannochloropsis sp. reaches 80% of dry weight and has the sama characteristics as vegetable oil. In the lipid extraction process many problems were found, one of which was the cell wall of Nannochloropsis sp. which prevents the lipid from being extracted. This research was carried out on 10 December 2022-28 February 2023 at the Hatchery and Aquaculture Technology Laboratory aquaculture study program, faculty of agrigulture, Malikussaleh University, Chemical Technology Laboratory at Lhokseumawe State Polytechnic and at The Environmental Quality Testing Engineering Laboratory At Syiah Kuala University, Banda Aceh. This study used a laboratory experimental method using a Non-Factorial Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications. Treatment A Control, treatment B Heating, treatment C Osmotic shock and treatment D Homogenizer. Based on statistical analysis of the F test (ANOVA) showed that the percentage of lipid from the application of pretreatment gave significantly different resulst to the percentage of lipid from the application of pretreatment. The highest lipid was found in treatment B which was 21,14% and the lowest lipid was in treatment C which was 12,51%. The highest lipid producer from the application of pretreatment is using the heating method. Biodiesel is obtained through a tranesterification process using methanol as a solvent and KOH catalyst.